SOME CLINICAL AND LABORATORY FEATURES OF THE COURSE OF SEROUS MENINGITIS OF ENTEROVIRUS ETIOLOGY IN CHILDREN (Multidisciplinary Journal of Science and Technology, 2024)
This article examines an examination of 16 patients aged 1 to 14 years with a laboratory confirmed (cerebrospinal fluid PCR) diagnosis of enterovirus meningitis. All patients, depending on age, were divided into 3 groups. The main group of cases was made up of school children. The course of the disease in all cases is benign with a short febrile period, a short period of clinically pronounced meningeal syndrom.